Physiological and biochemical characterization of NERICA-L-44: a novel source of heat tolerance at the vegetative and reproductive stages in rice - Bahuguna, Rajeev N.; Jha, Jyoti; Pal, Madan; Shah, Divya; Lawas, Lovely M.F.; Khetarpal, Sangeetha; Jagadish, Krishna S.V. (Wiley, 2015)
The predicted increase in the frequency and magnitude of extreme heat spikes under future climate can reduce rice yields significantly. Rice sensitivity to high temperatures during the reproductive stage is well documented while the same during the vegetative stage is more speculative. Hence, to identify and characterize novel heat‐tolerant donors for both the vegetative and reproductive stages, 71 rice accessions, including approximately 75% New Rice for Africa (NERICAs), were phenotyped across field experiments during summer seasons in Delhi, India, and in a controlled environment study at International Rice Research Institute, Philippines. NERICA‐L‐44 (NL‐44) recorded high seedling survival (52%) and superior growth and greater reproductive success exposed to 42.2°C (sd ± 2.3) under field conditions. NL‐44 and the heat‐tolerant check N22 consistently displayed lower membrane damage and higher antioxidant enzymes activity across leaves and spikelets. NL‐44 recorded 50–60% spikelet fertility, while N22 recorded 67–79% under controlled environment temperature of 38°C (sd±1.17), although both had about 87% fertility under extremely hot field conditions. N22 and NL‐44, exposed to heat stress (38°C), had similar pollen germination percent and number of pollen tubes reaching the ovary. NL‐44 maintained low hydrogen peroxide production and non‐photochemical quenching (NPQ) with high photosynthesis while N22 avoided photosystem II damage through high NPQ under high‐temperature stress. NL‐44 with its reproductive stage resilience to extreme heat stress, better antioxidant scavenging ability in both vegetative tissue and spikelets and superior yield and grain quality is identified as a novel donor for increasing heat tolerance at both the vegetative and reproductive stages in rice.